Formation of Lotus-Type Porous Iron by Zone Melting in a Nitrogen Atmosphere - Yingjie Pan; Yuchong Chen; Qinglin Jin (Metals)
Traditional lotus-type porous materials are typically fabricated under a hydrogen atmosphere, which poses safety risks. In contrast, using nitrogen enhances safety but often results in lower porosity and irregular pore shapes. This study investigates the fabrication of lotus-type porous iron using the zone melting technique under a nitrogen atmosphere, exploring the effects of nitrogen pressure and withdrawal rate on pore morphology. The results show that higher nitrogen pressure and a lower withdrawal rate lead to more regular and uniform pores. At 1.0 MPa nitrogen pressure and a 5 mm/min withdrawal rate, the most regular pore morphology was achieved, with porosity reaching 35%. Furthermore, as the nitrogen pressure increases, the nitrogen content and micro-Vickers hardness of the material increase significantly, exhibiting a pronounced solid solution strengthening effect. At 1.0 MPa, the nitrogen content reaches 0.077 wt.%, and the hardness increases from 136 HV for pure iron to 192 HV. Theoretical analysis suggests that stable pore growth is achieved when the product of nitrogen pressure and withdrawal rate is less than a constant. Increasing the nitrogen pressure promotes nitrogen dissolution in the molten zone, while a lower withdrawal rate facilitates adequate nitrogen diffusion, ensuring stable pore growth and higher porosity. This study provides a foundation for fabricating lotus-type porous materials using nitrogen as a safer alternative to hydrogen.